Logistics and supply chain management in the globalized business era - Wood, Lincoln C.; Duong, Linh Nguyen Khanh, 1985- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This publication covers both strategic and operational level elements of logistics and supply chain research, providing a comprehensive overview of the field with particular attention to new technologies, digitization, and optimization as applied in the era of globalized business"--